2011
DOI: 10.1002/jobm.201100097
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba polyphaga, a potential environmental vector for the transmission of food‐borne and opportunistic pathogens

Abstract: The endosymbiotic relationship could represent for many bacteria an important condition favouring their spread in the environment and in foods. For this purpose we studied the behaviour of some food-borne and opportunistic pathogens (Listeria monocytogenes, Staphylococcus aureus, Enterococcus faecalis, Salmonella enterica serovar Enteritidis, Aeromonas hydrophila, Yersinia enterocolitica) when internalized in Acanthamoeba polyphaga. Our results confirm the capability of the bacteria tested to grow within amoeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 51 publications
5
27
1
Order By: Relevance
“…Survival and growth of S. aureus in Acanthamoeba spp. (Anacarso et al, 2012;Cardas et al, 2012;Huws et al, 2006) and H. vermiformis (Pickup et al, 2007), both organisms present on dishcloths, was observed. Campylobacter spp.…”
Section: Discussionmentioning
confidence: 94%
“…Survival and growth of S. aureus in Acanthamoeba spp. (Anacarso et al, 2012;Cardas et al, 2012;Huws et al, 2006) and H. vermiformis (Pickup et al, 2007), both organisms present on dishcloths, was observed. Campylobacter spp.…”
Section: Discussionmentioning
confidence: 94%
“…Two Acanthamoeba species were chosen based on previous studies. A. castellanii is reported to have interactions with nonenveloped viruses (human enteroviruses and adenoviruses) of significance to public health (25,30,31), while both A. castellanii and A. polyphaga play a role in many interactions between acanthamoebae and food-borne bacteria (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria implicated in food-borne disease outbreaks that have been reported to interact with Acanthamoeba include enterohemorrhagic Escherichia coli (27), Salmonella enterica subsp. enterica, Listeria monocytogenes, Clostridium botulinum, and Campylobacter jejuni (26,28,29). Studies involving Acanthamoeba interactions with viruses are much more limited, including poliovirus, echoviruses 4 and 30 (30), adenoviruses 11 and 41 (31), and coxsackievirus B3 (25).…”
mentioning
confidence: 99%
“…Many wellknown pathogens of humans are able to infect, survive, and multiply within phagocytosis vacuoles Horn and Wagner, 2004). FLA serve as reservoirs and vectors for the transmission of pathogenic bacteria to humans or animals (Lorenzo-Morales et al, 2007;Thomas and Greub 2010;Anacarso et al, 2012;Mella et al, 2016). Several publications appeared in recent years documenting that amoeba can serve as a genetic "melting pot" where gene exchanges occur.…”
Section: Introductionmentioning
confidence: 99%